2007
DOI: 10.1007/s00508-007-0807-2
|View full text |Cite
|
Sign up to set email alerts
|

High eradication rate of H. pylori with moxifloxacin-based treatment: a randomized controlled trial

Abstract: Moxifloxacin-based triple therapies showed higher eradication rates with few side effects and good drug compliance when compared with standard H. pylori treatments. Moreover, the increased prevalence of clarithromycin resistance suggests that moxifloxacin-based regimens could be safe and effective options in treatment of H. pylori infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 30 publications
6
33
0
1
Order By: Relevance
“…And the data on the primary resistance to moxifloxicin are limited. Only Bago et al reported a low resistance rate of 5.9% in Croatia, as far as we know (21).…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…And the data on the primary resistance to moxifloxicin are limited. Only Bago et al reported a low resistance rate of 5.9% in Croatia, as far as we know (21).…”
Section: Introductionmentioning
confidence: 68%
“…Of seven potential eligible articles, we excluded two more articles as the moxifloxacin-based therapy was used as second-line treatment for Helicobacter pylori infection (23,26) and one paper without standard triple therapy as contrast group (24). Finally, four RCTs (n=772 patients) were included which compared moxifloxacin-based triple therapy to clarithromycin-based triple therapy (21,27,29,35). The quality of the included studies is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations